Peran Keberagaman Gender Didalam Memoderasi Kinerja Environment Social, Dan Governance Terhadap Resiko Keuangan - Shafira Choirun Nissa; Suwarno (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to determine the role of gender diversity in moderating the performance of the social environment, and governance on financial risk. This research approach is quantitative by using secondary data. ESG data and financial risks will be obtained from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) during a certain period, for example 2018–2023. This study uses a moderated regression analysis (MRA) approach to examine the influence of gender diversity moderation on the relationship between ESG performance. This study reveals that gender diversity has a significant moderating influence on the relationship between Environmental, Social, and Governance (ESG) performance and corporate financial risk.